Editorial [Hot Topic: Latest Developments in Pharmaceutical Design of Arachidonic Acid Metabolites: Prostaglandins, Thromboxanes, Hepoxilins and Isoprostanes (Executive Editors: J.-M. Dogne and K.-H. Ruan )] - Dogne, Jean-Michel; Ruan, Ke-He (Current Pharmaceutical Design, 2006)
In response to hormonal stimulation, phospholipases are activated to release arachidonic acid from membrane phospholipids. Free arachidonate can then metabolized nonenzymatically, contributing to oxidative stress, or through the actions of different types of oxygenase: cyclooxygenase (COX), lipoxygenase (LOX), and cytochrome P450 monooxygenases. The arachidonic acid metabolites produced, or eicosanoids, are a large series of lipidderived mediators capable of producing a multitude of physiologic effects in the local environment. They play important roles in a variety of signaling pathways both in physiologic and pathophysiologic conditions. For many years, arachidonic acid metabolism has become one of the most active area of fundamental and applied research. Researchers and pharmaceutical companies early focused their attention on new agents able to interfere with metabolic steps in the degradation of arachidonic acid or eicosanoid receptors. The aim of this hot topic is to highlight the latest developments in the pharmaceutical design of some specific arachidonic acid pathway metabolites or enzymes. Thus, over a decade ago, Professor Jason D. Morrow reported that a series of prostaglandin (PG)1-like compounds were produced by the free radical-catalyzed peroxidation of arachidonic acid, independent of the cyclooxygenase enzyme. Since then, this researcher and others have accumulated a large body of evidence indicating that quantification of these unique products of lipid peroxidation, now termed isoprostanes, provides a reliable marker of oxidant injury both in vitro and in vivo. In the first review, the mechanisms involved in isoprostanes formation, their biological activities at a cellular level and the future research related to the development of pharmacological approaches to modulate their formation and action in vivo will be discussed [1]. Thromboxane A2 (TXA2) and prostacyclin (PGI2) are two key metabolites produced by the cyclooxygenase pathway via thromboxane synthase and prostacyclin synthase, respectively. TXA2 has been implicated in various pathophysiological conditions due to its potent activating effects on platelet aggregation and smooth muscle contraction. In the second review of this hot topic, Dr. Jean-Michel Dogné, co-guest editor, aims to describe the physiological properties of TXA2, thromboxane synthase and thromboxane receptors [2]. Two sections are dedicated to a presentation of each class of TXA2 modulators with the advantages and disadvantages they offer and to recent studies performed with the most interesting TXA2 modulators in major pathologies such as myocardial infarction and thrombosis, atherosclerosis, diabetes, pulmonary embolism, septic shock, preeclampsia, and asthma. PGI2 is the main arachidonic acid metabolite in vascular walls and has opposing biological properties to TXA2. Indeed, PGI2 represents the most potent endogenous inhibitor of platelet aggregation and is also a strong antihypertensive agent through its vasodilatory effects on vascular beds. Understanding the molecular mechanisms of PGI2 biosynthesis and signaling is crucial to the development of therapeutic approaches to regulate PGI2 functions. Thus, Dr. Ke-He Ruan, co-guest editor provides information regarding the most current advances in the findings of the molecular mechanisms for PGI2 biosynthesis and for PGI2 signaling through its cell membrane receptors and nuclear peroxisome proliferator-activated receptors [3]. Prostaglandin E2 is the most common prostanoid with a variety of bioactivities and has been implicated in various pathologies. Prostaglandin E synthase (PGES), which converts cyclooxygenase (COX)-derived prostaglandin H2 to PGE2, occurs in multiple forms with distinct enzymatic properties, modes of expression, cellular and subcellular localizations and intracellular functions. In their review, Makoto Murakami and Dr. Ichiro Kudo highlight the latest understanding of the expression, regulation and functions of these three PGES enzymes, in particular mPGES-1 of which recent gene targeting studies have revealed that this enzyme represents a novel target for anti-inflammatory and anti-cancer drugs [4]. Prostaglandins, PGI2, TXA2 and lipoxins are rapidly metabolized by initial oxidation of their 15(S)-hydroxyl group catalyzed by NAD+-linked 15-hydroxyprostaglandin dehydrogenase (15-PGDH). The 15-keto products of this enzyme exhibit greatly reduced biological activities. Therefore, this enzyme has been considered the key enzyme responsible for the inactivation of these biologically active eiocosanoids. Moreover, studies on the regulation of enzyme expression and activity by physiological and pharmacological agents have begun to uncover its significant roles in cancer, inflammation and reproduction. In the fifth review, Dr. Hsin-Hsiung Tai provides insight into structural characterization, transcriptional regulation, biological functions and catalytic mechanism of this enzyme...... [5].